“Barbaric” cultural practices: Culturalizing violence and the failure to protect women in Canada - Mattoo, Deepa; Merrigan, Sydele (International Journal of Child, Youth and Family Studies, 2021)
The introduction of Bill S-7, the Zero Tolerance for Barbaric Cultural Practices Act, in 2015 garnered major critical attention across Canada. Amid an already tense climate of anti-immigrant sentiment in the post-9/11 era, the title chosen for the bill by the Conservative-led government catalyzed xenophobia, perpetuated the “us versus them” rhetoric, and culturalized violence. While originally touted as an opportunity to enhance protection for girls and women against the “foreign” horrors of polygamy, early and forced marriage, and “honour”-based killings, Bill S-7 instead fanned the flames of xenophobia on a mass level, failed to protect women, and, in fact, created higher risk of harms for women who are victims of gender- or family-based violence. In this commentary, we provide an overview of Bill S-7, the amendments to legislation made as a result of its passing, and some of its many problematic elements. We address the barriers to disclosing violence in racialized communities and subsequently provide suggestions on how to effectively address gender- and family-based violence in Canada in an effort to support survivors and prevent further harm.